Zagubione w prezkladzie - Hoffman, Eva, 1945- (Londyn : Aneks, 1995)
An autobiographical memoir of a Polish Jewish author who left Poland at the age of 13.
Originally published in English: New York : Dutton, 1989.
Translated from the English: Michal Ronikier.
Keywords: Polish people -- United States -- Biography; Immigrants -- United States -- Biography; Jews -- United States -- Biography; Children of Holocaust survivors -- Poland -- Biography; Children of Holocaust survivors -- United States -- Biography